The importance of teamwork in sports - Abdul Talib, Nurafida; Abdullah, Nasiha; Ngah, Nazlin Emieza; Adenan, Nur Dalila; Mohamad Azmin, Nur Azwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2024)
The team's collective strength ultimately surpasses that of its individual members. This principle applies to all sports teams. While having a talented group of athletes is crucial,fostering teamwork is equally essential for achieving success as a cohesive unit. The key to success lies in team spirit which requires members to unite in facing opponents together.